Multi-trait association study identifies loci associated with tolerance of low phosphorus in Oryza sativa and its wild relatives - Anandan, Annamalai; Nagireddy, Ranjitkumar; Sabarinathan, Selvaraj; Bhatta, Bishal Binaya; Mahender, Anumalla; Vinothkumar, Murugapandiyan; Parameswaran, Chidambaranathan; Panneerselvam, Periyasamy; Subudhi, Hatanath; Meher, Jitendriya; Bose, Lotan Kumar; Ali, Jauhar (Springer, 2022)
We studied variation in adaptive traits and genetic association to understand the low P responses, including the symbiotic association of arbuscular mycorrhizal (AM) fungal colonization inOryzaspecies (O. sativa,O. nivara,andO. rufipogon). In the present experiment, we performed the phenotypic variability of the morphometric and geometric traits for P deficiency tolerance and conducted the association studies in GLM and MLM methods. A positive association between the geometric trait of the top-view area and root traits suggested the possibility of exploring a non-destructive approach in screening genotypes under low P. The AMOVA revealed a higher proportion of variation among the individuals as they belonged to different species ofOryzaand the NM value was 2.0, indicating possible gene flow between populations. A sub-cluster with superior-performing accessions had a higher proportion of landraces (42.85%), andO. rufipogon(33.3%) was differentiated by fourPup1-specific markers. Association mapping identified seven notable markers (RM259, RM297, RM30, RM6966, RM242, RM184, and PAP1) and six potential genotypes (IC459373, Chakhao Aumbi, AC100219, AC100062, Sekri, and Kumbhi Phou), which will be helpful in the marker-assisted breeding to improve rice for P-deprived condition. In addition, total root surface area becomes a single major trait that helps in P uptake under deficit P up to 33% than mycorrhizal colonization. Further, the phenotypic analysis of the morphometric and geometric trait variations and their interactions provides excellent potential for selecting donors for improving P-use efficiency. The identified potential candidate genes and markers offered new insights into our understanding of the molecular and physiological mechanisms driving PUE and improving grain yield under low-P conditions.